Industrialization During the Implementation of ASEAN Economic Community (AEC) Blueprint 2015 - Mutaqin, Muhammad Iqbal (Journal of Accounting Research, Organization and Economics, 2020)
Objective This paper examines whether the implemented ASEAN Economic Community AEC 2015 measures have a significant effect on ASEAN industrialization.Design/methodology The examination was performed by comparing the growth of manufacturing indicators before and after the period of the AEC Blueprint implementation. panel data was used to examine the trend of manufacturing development in ten ASEAN countries: Brunei Darussalam, Cambodia, Indonesia, Lao, Malaysia, Myanmar, Philippines, Singapore, Thailand, and Vietnam. The panel data analysis examined seventeen years data on ten ASEAN countries that reported manufacturing indicators (mnfemp, mnva, rmva), GDP per capita, and population. The AEC Blueprint is implemented in a specific timeline since the year 2008 by ASEAN countries.Results This study found that there are no significant differences in the growth of manufacturing employment and the growth of nominal manufacturing value-added before and after a period of AEC blueprint implementation. Also, the growth of the real manufacturing value-added in the period of AEC blueprint implementation is less than prior AEC era. The findings of this study support studies that criticize the AEC implementation.